Linear precoding for centralized multicell MIMO networks - Holakouei, Reza
The aim of this paper is to propose and evaluate multiuser linear precoding techniques for downlink of multicell MIMO based networks. We consider a high-speed backhaul network where the base stations are transparently linked by optical fiber to a central unit. This architecture allows an efficient joint multicell multiuser processing. The proposed precoder is designed in two phases: first the intercell interference is removed by applying a block diagonalization algorithm. Then the system is further optimized by proposing three power allocation algorithms with per-BS power constraint and different complexity tradeoffs: one optimal to minimize the BER and two suboptimal. The performance of the proposed schemes is evaluated, considering typical pedestrian scenarios based on LTE specifications. Numerical results show that the proposed suboptimal power allocation schemes achieve a performance close to the optimal. © 2011 IEEE.